Subject advantage in covert dependencies: the case of wh-questions comprehension in French Sign Language - Donati, Caterina; Hauser, Charlotte; Aristodemo, Valentina (Syntax (Oxford, England), 2022)
Languages of the world vary with respect to the position in which wh-expressions are displayed in content questions. In some languages they are typically dislocated in a peripheral position, while in others they are left in situ, and some languages allow for both options. Studies on sentence-processing have shown that, as all A-bar dependencies, content questions involving wh-movement display a subject advantage, but very little is known about wh-in situ questions. The aim of this paper is to fill in this gap and explore whether a subject advantage can be found in wh-in situ questions. It reports the results of a sentence-to-picture matching task with in situ whquestions in French Sign Language (LSF). Three adult populations with different age of exposure to sign language are included: native signers, early signers and late signers. Results show that comprehension of wh-in situ questions in LSF displays a subject advantage. This result is argued to be relevant for the analysis of wh-in situ, supporting a covert movement analysis against alternatives involving some instance of (unselective) binding. Moreover, comparison across populations show that delayed exposure to language has an impact on the comprehension of wh-questions, confirming that the effects of early language deprivation affect language competence in adulthood.